Lifestyle and Health - Martyna Gorzelak; Monika Pierzak (Kazimierz Wielki University, 2017)
Admission:  The World Health Organization defines lifestyle as a way of being associated with the interaction of man and the conditions, in which he lives, as well as individual behavior patterns, which have been determined by socio-cultural factors and personal characteristics charakter2. Aim: Aim of the study is to identify the impact of lifestyle on human health in every stage of life. Lifestyle is defined as all the characteristics of the behavior of a particular individual or community. It refers to behavior occurring in everyday life and those routinely repeated. The lifestyle behaviors include inter alia: attitudes to work and use, leisure, nutrition, clothing and relationships. Summary: Healthy lifestyle developed among people of all ages, will transfer into later adult health, their children, and the elderly. A healthy lifestyle improves the quality of life in every stage.